Hospital factors and metastatic surgery in colorectal cancer patients, a population-based cohort study - Malin Ljunggren; Caroline E. Weibull; Emma Rosander; Gabriella Palmer; Bengt Glimelius; Anna Martling; Caroline Nordenvall (BMC Cancer)
Abstract Background Only a limited proportion of patients with metastatic colorectal cancer (mCRC) receives metastatic surgery (including local ablative therapy). The aim was to investigate whether hospital volume and hospital level were associated with the chance of metastatic surgery. Methods This national cohort retrieved from the CRCBaSe linkage included all Swedish adult patients diagnosed with synchronous mCRC in 2009–2016. The association between annual hospital volume of incident mCRC patients and the chance of metastatic surgery, and survival, were assessed using logistic regression and Cox regression models, respectively. Hospital level (university/non-university) was evaluated as a secondary exposure in a similar manner. Both uni- and multivariable (adjusted for sex, age, Charlson comorbidity index, year of diagnosis, cancer characteristics and socioeconomic factors) models were fitted. Results A total of 1,674 (17%) out of 9,968 mCRC patients had metastatic surgery. High hospital volume was not associated with increased odds of metastatic surgery after including hospital level in the model, whereas hospital level was (odds ratio (OR) (95% confidence interval (CI)): 1.94 (1.68–2.24)). All-cause mortality was lower in university versus non-university hospitals (hazard ratio (95% CI): 0.83 (0.78–0.88)). Conclusions Patients with mCRC initially cared for by a university hospital experienced a greater chance to receive metastatic surgery and had superior overall survival. High hospital volume in itself was not associated with a greater chance to receive metastatic surgery nor a greater survival probability. Additional efforts should be imposed to provide more equal care for mCRC patients across Swedish hospitals.